In-situ synthesis Al2O3 reinforced low-density steel-based composite material and preparation method thereof
By generating Al2O3 enhanced phase particles through in-situ reaction in the steel matrix, the problems of poor dispersion and insufficient binding strength of Al2O3 particles in the prior art are solved, and efficient preparation and performance improvement of steel matrix composite materials are achieved.
Patent Information
- Application Number
- CN202411599095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
AI Technical Summary
In the preparation of existing Al2O3 reinforced steel-based composite materials, the dispersion of Al2O3 particles is poor, resulting in unsatisfactory mechanical properties and uniformity of the finished product, insufficient bonding strength, which may lead to interface peeling or cracks, affecting the performance of the composite materials, and the process is complex and costly, making it difficult to carry out large-scale production.
In situ reaction casting method is used, metal oxide molten salt is used as the O element source, and Al2O3 reinforced phase particles are generated in the steel matrix through in situ reaction during the casting process, achieving a good combination of Al2O3 reinforced phase particles and steel matrix, simplifying the process flow and reducing costs.
The good combination of Al2O3 enhanced phase particles and steel matrix is achieved, which improves the overall performance of the material, including tensile strength, elongation and hardness, while reducing material density, simplifying the process flow, and reducing production costs.
Smart Images

Figure CN119571201A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal-based composite materials, and more specifically to an in-situ self-generated Al2O3-reinforced low-density steel-based composite material and a preparation method thereof. Background Art
[0002] Steel is a common structural material, but its high density limits its application in lightweight applications. In the design of low-density steel, adding low-density alloying elements to steel becomes the most direct choice. Among the many alloying elements, Al (density 2.7g / mm 3 ) has a high solid solubility in Fe, so it has become the most studied additive element. Related studies have shown that for every 1% increase in Al, the density of steel can be reduced by 1.3%. If the steel contains 8% aluminum, the density of the steel can be reduced to 7g / mm 3 However, adding a large amount of Al to the steel will produce a brittle second phase, which will lead to a loss of material elongation.
[0003] In order to improve the strength and lightweight performance of steel, researchers have proposed a method of combining steel-based composites with lightweight reinforcement. The commonly used method for preparing Al2O3-reinforced steel-based composites is powder metallurgy. The Al2O3 particles in the composites prepared by this method are not well dispersed in the steel matrix, resulting in unsatisfactory mechanical properties and uniformity of the finished product. The bonding strength between the Al2O3 particles and the steel matrix is not strong enough, which may cause interface peeling or cracks, affecting the performance of the composite material. The density after sintering is not enough, and there are pores or defects, which affect its mechanical properties and corrosion resistance. Poor control of in-situ reaction conditions during the preparation process will affect the generation and distribution of Al2O3 particles. In addition, powder metallurgy often has problems such as high cost and complex process, and is not easy to carry out large-scale production. Summary of the invention
[0004] In view of the defects existing in the prior art, the purpose of the present invention is to provide an in-situ self-generated Al2O3 reinforced low-density steel-based composite material and a preparation method thereof, using metal oxide molten salt as a raw material to introduce an O source, and generating Al2O3 reinforcing phase particles in the steel matrix through in-situ reaction during the casting process, thereby achieving a good combination of the Al2O3 reinforcing phase particles and the steel matrix, and improving the overall performance of the material while ensuring the low density of the steel-based composite material.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] A first aspect of the present invention provides an in-situ self-generated Al2O3-reinforced low-density steel-based composite material, which comprises a steel matrix and an Al2O3 reinforcement phase distributed in the steel matrix;
[0007] The steel matrix is high-aluminum steel, and the Al content of the high-aluminum steel is 8-13wt.%;
[0008] The Al2O3 reinforcement phase is generated by in-situ reaction between oxygen elements in the metal oxide molten salt and aluminum elements in the high-aluminum steel melt during the smelting process, and the volume percentage of the Al2O3 reinforcement phase in the steel matrix is 10-20%.
[0009] Preferably, the metal oxide molten salt is selected from one or more of copper oxide, lanthanum oxide and iron oxide.
[0010] Preferably, the average particle size of the Al2O3 reinforcement phase is 5 to 10 μm.
[0011] Preferably, the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.8-7.2 g / cm 3 , tensile strength is 800~1000MPa, elongation is 25%~35%, and hardness is 280HV~320HV.
[0012] The second aspect of the present invention provides a method for preparing the in-situ self-generated Al2O3 reinforced low-density steel-based composite material as described in the first aspect of the present invention, comprising the following steps:
[0013] S1, mixing metal oxide molten salt powder, metal aluminum powder and metal iron powder uniformly by ball milling to obtain a mixed powder;
[0014] S2, vacuum drying the mixed powder, and adding paraffin wax to the mixed powder for doping;
[0015] S3, drying the mixed powder doped with paraffin wax in an air environment, then stirring it evenly and pressing it into blocks to obtain pre-pressed blocks;
[0016] S4, placing the pre-pressed block, pure aluminum block and pure iron block in an induction furnace for smelting, during the smelting process, the metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, and after the smelting is completed, casting is performed to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0017] Preferably, in step S1:
[0018] The mass ratio of the metal oxide molten salt to the metal aluminum powder and the metal iron powder is 10-20:10-20:60-80;
[0019] The particle sizes of the metal oxide molten salt, metal aluminum powder and metal iron powder are all 9 to 20 μm;
[0020] In the ball milling process, the ball milling time is ≥6 hours, and the ball-to-material ratio is 3 to 15:1.
[0021] Preferably, in step S2:
[0022] The vacuum degree during vacuum drying is 1×10 -1 ~1×10 2 Pa;
[0023] The mass ratio of the mixed powder to paraffin is 90-100:1.
[0024] Preferably, in step S3:
[0025] During the drying process, the drying temperature is 70-100°C;
[0026] During the pressing process, the pressing pressure is 25-50 MPa.
[0027] Preferably, in step S4:
[0028] The mass ratio of the pre-pressed block, the pure aluminum block, and the pure iron block is 5-7:8-13:87-92;
[0029] In the smelting process, the smelting temperature is 1550-1650° C., the smelting time is 20-30 min, and the heating rate from room temperature to the smelting temperature is 30-50° C. / min.
[0030] The present invention uses oxide molten salt powder (one or more of copper oxide, lanthanum oxide, and iron oxide) and metal aluminum, metal iron, etc. as raw materials; the oxide molten salt powder and metal aluminum and metal iron powder are ball-milled and mixed evenly, and vacuum dried; paraffin is added to the mixed powder for doping, and after drying at 70-100° C., it is stirred evenly and pressed into blocks; the prefabricated blocks and metal aluminum blocks and metal iron blocks are melted and cast in an induction furnace to obtain an in-situ self-generated Al2O3-reinforced low-density steel-based composite material; the specific beneficial effects are as follows:
[0031] 1. The present invention simplifies the process flow by using the in-situ reaction casting method. It does not need to pre-synthesize or mix the strengthening phase. The strengthening phase is formed directly in the casting process through appropriate reaction conditions, which saves production steps and costs. The use of in-situ synthesis technology in the traditional casting method can make the distribution of the strengthening phase more uniform, make the strengthening phase more firmly combined with the matrix material, and can more effectively play the role of the strengthening phase, so that the mechanical properties of the material are improved to a greater extent.
[0032] 2. The present invention creatively selects different types of metal oxide molten salts and pre-treats the raw materials to achieve good bonding between the Al2O3 reinforcement phase particles generated by in-situ autogenous reaction in the traditional casting process and the low-density steel matrix, thereby improving the overall performance of the material;
[0033] 3. The present invention first mixes the metal oxide molten salt with pure aluminum powder and pure iron powder and then presses them into blocks, which can increase the mutual contact area of the reactants in the melt. The pre-pressed block contains a certain amount of iron powder, which can increase the density of the pre-pressed block and make it easier to add it into the melt instead of floating on the surface of the melt, so that the metal oxide molten salt reacts with aluminum more thoroughly, thereby effectively improving the efficiency of preparing Al2O3 reinforcement phase particles by in-situ autogenous reaction;
[0034] 4. The in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared by the present invention has an Al2O3 reinforcement phase particle content of 10 to 20 vol.%, a micron-sized particle, and better interface bonding between the Al2O3 reinforcement phase particles and the steel matrix, ultimately reducing the density of the steel-based composite material while improving its strength, elongation and hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic flow chart of a method for preparing an in-situ self-generated Al2O3-reinforced low-density steel-based composite material of the present invention;
[0036] Figure 2 1 is a SEM-EDS image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in Example 1 of the present invention, (a) is a SEM image of the low-density steel-based composite material, (b) is an O element distribution image in the low-density steel-based composite material, and (c) is an Al element distribution image in the low-density steel-based composite material;
[0037] Figure 3 1 is a SEM-EDS line scan of the interface between the reinforcing phase and the high-aluminum steel of the in-situ self-generated Al2O3-reinforced low-density steel-based composite material prepared in Example 1 of the present invention; (a) is a high-magnification SEM image of the interface between the reinforcing phase and the high-aluminum steel of the low-density steel-based composite material, (b) is an energy spectrum analysis of Al at the EDS line in Figure (a); (c) is an energy spectrum analysis of Fe at the EDS line in Figure (a); (d) is an energy spectrum analysis of O at the EDS line in Figure (a);
[0038] Figure 4 is the stress-strain curve of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in Example 1 of the present invention;
[0039] Figure 5 is a SEM image of the Al2O3 reinforced steel-based composite material prepared in Comparative Example 1;
[0040] Figure 6 The hardness of the Al2O3 reinforced steel-based composite material with different Al2O3 addition amounts prepared in Comparative Example 2 before and after quenching;
[0041] Figure 7is a SEM image of the 15 vol.% Al2O3 reinforced steel-based composite material prepared in Comparative Example 2;
[0042] Figure 8 This is a SEM image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in Comparative Example 3;
[0043] Fig. 9 This is a SEM image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in Comparative Example 4. DETAILED DESCRIPTION
[0044] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0045] The present invention utilizes an in-situ reaction casting method, which can simplify the process flow. It does not require pre-synthesis or mixing of the strengthening phase, but directly realizes the formation of the strengthening phase during the casting process through appropriate reaction conditions, saving preparation steps and costs. The present invention uses in-situ synthesis technology during the casting process to make the distribution of the strengthening phase more uniform, make the strengthening phase and the matrix material more firmly combined, can more effectively play the role of the strengthening phase, and improve the mechanical properties of the material to a greater extent. The present invention uses an in-situ reaction casting method to prepare steel-based composite materials, which provides a new way for the preparation and application of new composite materials. The present invention creatively selects different types of metal oxide molten salts, and through certain treatment of the raw materials, realizes the good combination of Al2O3 strengthening phase particles generated by in-situ autogenous reaction in the traditional casting process and the low-density steel matrix, and improves the overall performance of the material.
[0046] The present invention provides an in-situ self-generated Al2O3 reinforced low-density steel-based composite material, which comprises a steel matrix and an Al2O3 reinforcement phase distributed in the steel matrix; the steel matrix is high-aluminum steel, and the Al content of the high-aluminum steel is 8-13wt.%; the Al2O3 reinforcement phase is generated by in-situ reaction of oxygen elements in metal oxide molten salt and aluminum elements in high-aluminum steel melt during smelting, and the volume percentage of the Al2O3 reinforcement phase in the steel matrix is 10-20%.
[0047] The above-mentioned metal oxide molten salt is selected from one or more of copper oxide, lanthanum oxide and iron oxide.
[0048] The average size of the Al2O3 reinforcement phase is 5 to 10 μm. The Al2O3 reinforcement phase is generated by in-situ reaction during the casting process. The surface of the ceramic particles (i.e., the Al2O3 reinforcement phase) is pollution-free and has good compatibility with the low-density steel matrix. The interface bonding strength is high. Compared with the existing powder metallurgy method for preparing Al2O3 reinforced steel-based composite materials, it can reduce pore defects and is conducive to improving the overall strength of the material.
[0049] The density of the above-mentioned in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.8-7.2 g / cm 3 , tensile strength is 800~1000MPa, elongation is 25%~35%, and hardness is 280HV~320HV.
[0050] Combination Figure 1 As shown, the preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of the present invention comprises the following steps:
[0051] S1, mixing metal oxide molten salt powder, metal aluminum powder and metal iron powder uniformly by ball milling to obtain a mixed powder;
[0052] In this step, metal oxide molten salt powder, metal aluminum powder, and metal iron powder are selected as raw materials. The metal aluminum powder and metal oxide molten salt are used as Al and O element sources, respectively, and the metal iron powder is used as a reaction medium. The contact area of the reactants in the melt can be increased to increase the reaction rate. On the other hand, the addition of metal iron powder to the prefabricated block can increase the density and mass of the prefabricated block, making it easier to add it to the low-density molten steel during the smelting process, rather than floating on the surface of the melt, so that the metal oxide molten salt reacts more thoroughly with the aluminum in the melt, thereby effectively improving the efficiency of the in-situ autogenous reaction to generate the Al2O3 reinforcement phase.
[0053] Metal oxide molten salt powder (one or more of copper oxide, lanthanum oxide, and iron oxide) is ball-milled and mixed with metal aluminum and metal iron powder to obtain a mixed powder; wherein the particle sizes of the metal oxide molten salt, metal aluminum powder, and metal iron powder used are all 9-20 μm, and the mass ratio of the metal oxide molten salt to the metal aluminum powder and metal iron powder is 10-20:10-20:60-80; in the above ball milling process, the ball milling time is ≥6 hours, and the ball-to-material ratio is 3-15:1.
[0054] S2, vacuum drying the mixed powder, and adding paraffin wax to the mixed powder for doping;
[0055] In this step, the raw materials are processed and paraffin wax is added to the mixed powder. The addition of paraffin wax helps to increase the fluidity of the powder and the uniformity during pressing, making the powder easier to form and maintain its shape when pressed. On the other hand, it helps to maintain the mechanical strength of the prefabricated block and prevent it from breaking before the melt is added. The mixed powder is vacuum dried and the vacuum degree is controlled to 1×10 -1 ~1×10 2 Pa, removing surface moisture and volatile substances; and adding paraffin wax to the mixed powder for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 90-100:1.
[0056] S3, drying the mixed powder doped with paraffin wax in an air environment, then stirring it evenly and pressing it into blocks to obtain pre-pressed blocks;
[0057] In this step, the mixed powder doped with paraffin is dried in an air environment at a drying temperature of 70-100° C. After drying, it is stirred evenly and pressed into blocks at a pressing pressure of 25-50 MPa to obtain pre-pressed blocks.
[0058] The above-mentioned cold pressing method can make it easier for the metal oxide molten salt to be added to the melt in the subsequent smelting process, so that the Al2O3 reinforcement phase generated in the melt is evenly distributed in the low-density steel matrix.
[0059] S4, placing the pre-pressed block, pure aluminum block and pure iron block in an induction furnace for melting. During the melting process, the metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase. After the melting is completed, casting is performed to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0060] In this step, the Al2O3 reinforcement phase is mainly generated by in-situ reaction during the casting process. The pre-pressed block, pure aluminum block and pure iron block are placed in an induction furnace for melting. The temperature in the induction furnace is heated from room temperature to 1550-1650°C at a heating rate of 30-50°C / min, and then the melting temperature is maintained at 1550-1650°C for 20-30 minutes. During the melting process, the metal oxide molten salt reacts with Al in the melt to generate the Al2O3 reinforcement phase in situ. Then, the steel melt containing the Al2O3 reinforcement phase is poured into a graphite mold. After cooling at room temperature, an in-situ self-generated Al2O3-reinforced low-density steel-based composite material is obtained; wherein, the mass ratio of the pre-pressed block, pure aluminum block and pure iron block is 5-7:8-13:87-92.
[0061] The SEM characterization test and performance test of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material obtained above show that the material contains in-situ self-generated Al2O3 reinforcement phase, the volume percentage of Al2O3 reinforcement phase particles is 10% to 20%, the size is micron-level, the average size is 5 to 10μm, and the Al2O3 reinforcement phase particles are well bonded to the steel matrix; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.8 to 7.2 g / cm 3 , the tensile strength is 800~1000MPa, and the elongation is 25%~35%.
[0062] The in-situ self-generated Al2O3 reinforced low-density steel-based composite material and its preparation method of the present invention are further described below in conjunction with specific embodiments.
[0063] Example 1
[0064] The preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is as follows:
[0065] Step 1: Ball-mill the copper oxide powder, aluminum powder and iron powder to obtain a mixed powder. The ball-milling time is 6 hours and the ball-to-material ratio is 5:1. The mass ratio of copper oxide powder to aluminum powder and iron powder is 15:15:70. The particle sizes of copper oxide powder, aluminum powder and iron powder are all 10 μm.
[0066] Step 2: Dry the mixed powder after ball milling in step 1 at a vacuum degree of 1×10 -1 Pa, removal of surface moisture and volatile substances;
[0067] Step 3: adding paraffin wax to the mixed powder after vacuum drying in step 2 for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 100:1;
[0068] Step 4: drying the mixed powder doped with paraffin in step 3 in an air environment at a drying temperature of 70° C.
[0069] Step 5: Stir the mixed powder dried in step 4 and press it into blocks to obtain pre-pressed blocks, with a pressing pressure of 35 MPa;
[0070] Step 6: Place the pre-pressed block in step 5 and the pure aluminum block and pure iron block in an induction furnace at a mass ratio of 5:10:90 for melting. The melting temperature is 1550°C, the heating rate is 40°C / min, and the melting time is 20min. The metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, so that the Al2O3 reinforcement phase grows in situ in the low-density steel melt.
[0071] Step 7: pouring the Al2O3 reinforced low-density steel melt in step 6 into a graphite mold and cooling it at room temperature to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0072] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is 10.7wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.9g / cm 3 , tensile strength is 850MPa, elongation is 32.5%, hardness is 290HV. The average particle size of Al2O3 reinforcement phase particles is 5μm, and the volume percentage of Al2O3 reinforcement phase is 17.32%.
[0073] Combination Figure 2-Figure 4As shown, the in-situ self-generated Al2O3 reinforced low-density steel-based composite material consists of a low-density steel matrix and an Al2O3 reinforcement phase, and the low-density steel matrix is high-aluminum steel; the Al2O3 reinforcement phase is formed in situ in the high-aluminum low-density steel melt through the reaction of different types of molten salts and aluminum elements in the melt; the reactant molten salt and the medium (iron powder, aluminum powder) are processed by cold pressing, which makes it easier for the reactants to be added to the low-density steel melt during the smelting process; the Al2O3 reinforcement phase generated in situ in the melt is uniformly distributed in the low-density steel matrix.
[0074] Figure 2 This is the SEM-EDS image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment. It can be seen from the figure that a certain amount of Al2O3 reinforcement phase is generated in the steel matrix. The average particle size of the Al2O3 reinforcement phase particles is 5μm. According to ImagePro software statistics, the volume percentage of the Al2O3 reinforcement phase is 17.32%.
[0075] Figure 3 This is a SEM-EDS line scan image at high magnification of the interface between the Al2O3 reinforcement phase and the high aluminum steel in the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment. The line scan path passes through the low-density steel matrix, the interface between the Al2O3 reinforcement phase and the low-density steel, and the Al2O3 reinforcement phase. From the EDS line scan results, it can be seen that diffusion of the Fe element occurs at the interface, indicating that the interface bonding is good. Figure 3 (a) is a high-magnification SEM image of the interface between the reinforcement phase and the high-aluminum steel of the low-density steel matrix composite. It can be observed that there is an obvious transition zone at the interface between the reinforcement phase Al2O3 and the low-density steel matrix. Figure 3 The different characteristic peaks of (b), (c), and (d) show the changes in the relative concentrations of the three elements Fe, Al, and O. By comparing the SEM images, it can be found that there is obvious diffusion of Fe elements at the interface, which indicates that the bonding strength at the interface is relatively high.
[0076] Figure 4 3 is the stress-strain curve of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment. From the curve, it can be observed that the tensile strength of the low-density steel-based composite material can reach 850 MPa and the elongation can reach 32.5%.
[0077] Example 2
[0078] The preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is as follows:
[0079] Step 1: Ball-mill lanthanum oxide powder, aluminum powder and iron powder to obtain mixed powder. The ball-milling time is 7 hours and the ball-to-material ratio is 7:1. The mass ratio of lanthanum oxide powder to aluminum powder and iron powder is 20:20:60. The particle sizes of lanthanum oxide powder, aluminum powder and iron powder are all 11 μm.
[0080] Step 2: Dry the mixed powder after ball milling in step 1 at a vacuum degree of 1×10 -1 Pa, removal of surface moisture and volatile substances;
[0081] Step 3: adding paraffin wax to the mixed powder after vacuum drying in step 2 for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 97:1;
[0082] Step 4: drying the mixed powder doped with paraffin in step 3 in an air environment at a drying temperature of 75° C.
[0083] Step 5: Stir the mixed powder dried in step 4 and press it into blocks to obtain pre-pressed blocks, with a pressing pressure of 25 MPa;
[0084] Step 6: Place the pre-pressed block in step 5 and the pure aluminum block and the pure iron block in an induction furnace at a mass ratio of 5.5:11:89 for melting. The melting temperature is 1550°C, the heating rate is 30°C / min, and the melting time is 23min. The metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, so that the Al2O3 reinforcement phase grows in situ in the low-density steel melt.
[0085] Step 7: pouring the Al2O3 reinforced low-density steel melt in step 6 into a graphite mold and cooling it at room temperature to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0086] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is 10.5wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.97g / cm 3 , tensile strength is 870MPa, elongation is 31%, hardness is 287HV. The average particle size of Al2O3 reinforcement phase particles is 5.7μm, and the volume percentage of Al2O3 reinforcement phase is 16.2%.
[0087] Example 3
[0088] The preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is as follows:
[0089] Step 1: Ball-mill the iron oxide powder, aluminum powder and iron powder to obtain a mixed powder. The ball-milling time is 8 hours, and the ball-to-material ratio is 8:1. The mass ratio of iron oxide powder to aluminum powder and iron powder is 10:10:80. The particle sizes of iron oxide, aluminum powder and iron powder are all 15 μm.
[0090] Step 2: Dry the mixed powder after ball milling in step 1 at a vacuum degree of 1×10 -1 Pa, removal of surface moisture and volatile substances;
[0091] Step 3: adding paraffin wax to the mixed powder after vacuum drying in step 2 for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 95:1;
[0092] Step 4: drying the mixed powder doped with paraffin in step 3 in an air environment at a drying temperature of 70° C.
[0093] Step 5: Stir the mixed powder dried in step 4 and press it into blocks to obtain pre-pressed blocks, with a pressing pressure of 40 MPa;
[0094] Step 6: Place the pre-pressed block in step 5 and the pure aluminum block and pure iron block in an induction furnace at a mass ratio of 6:12:88 for melting. The melting temperature is 1550°C, the heating rate is 35°C / min, and the melting time is 25min. The metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, so that the Al2O3 reinforcement phase grows in situ in the low-density steel melt.
[0095] Step 7: pouring the Al2O3 reinforced low-density steel melt in step 6 into a graphite mold and cooling it at room temperature to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0096] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is 11.8wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.87g / cm 3 , tensile strength is 900MPa, elongation is 29%, hardness is 304HV. The average particle size of Al2O3 reinforcement phase particles is 6.5μm, and the volume percentage of Al2O3 reinforcement phase is 10.9%.
[0097] Example 4
[0098] The preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is as follows:
[0099] Step 1: Ball-mill the copper oxide powder, aluminum powder and iron powder to obtain a mixed powder. The ball-milling time is 9 hours, and the ball-to-material ratio is 3:1. The mass ratio of copper oxide powder to aluminum powder and iron powder is 20:10:70. The particle sizes of copper oxide, aluminum powder and iron powder are all 17 μm.
[0100] Step 2: Dry the mixed powder after ball milling in step 1 at a vacuum degree of 1 Pa to remove surface moisture and volatile substances;
[0101] Step 3: adding paraffin wax to the mixed powder after vacuum drying in step 2 for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 93:1;
[0102] Step 4: drying the mixed powder doped with paraffin in step 3 in an air environment at a drying temperature of 80° C.
[0103] Step 5: Stir the mixed powder dried in step 4 and press it into blocks to obtain pre-pressed blocks, with a pressing pressure of 45 MPa;
[0104] Step 6: Place the pre-pressed block in step 5 and the pure aluminum block and pure iron block in an induction furnace at a mass ratio of 6.5:8:92 for melting. The melting temperature is 1550°C, the heating rate is 45°C / min, and the melting time is 28min. The metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, so that the Al2O3 reinforcement phase grows in situ in the low-density steel melt.
[0105] Step 7: pouring the Al2O3 reinforced low-density steel melt in step 6 into a graphite mold and cooling it at room temperature to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0106] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is 8.0wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 7.15g / cm 3 , tensile strength is 950MPa, elongation is 26.1%, hardness is 290HV. The average particle size of Al2O3 reinforcement phase particles is 7.2μm, and the volume percentage of Al2O3 reinforcement phase is 13.7%.
[0107] Example 5
[0108] The preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is as follows:
[0109] Step 1: Ball-mill the copper oxide powder, aluminum powder and iron powder to obtain a mixed powder. The ball-milling time is 10 hours, and the ball-to-material ratio is 15:1. The mass ratio of copper oxide powder to aluminum powder and iron powder is 15:10:75. The particle sizes of copper oxide, aluminum powder and iron powder are all 20 μm.
[0110] Step 2: Dry the mixed powder after ball milling in step 1 at a vacuum degree of 10 Pa to remove surface moisture and volatile substances;
[0111] Step 3: adding paraffin wax to the mixed powder after vacuum drying in step 2 for doping, wherein the mass ratio of the mixed powder to the paraffin wax is 90:1;
[0112] Step 4: drying the mixed powder doped with paraffin in step 3 in an air environment at a drying temperature of 100° C.
[0113] Step 5: Stir the mixed powder dried in step 4 and press it into blocks to obtain pre-pressed blocks, with a pressing pressure of 50 MPa;
[0114] Step 6: Place the pre-pressed block in step 5 and the pure aluminum block and pure iron block in an induction furnace at a mass ratio of 7:13:87 for melting. The melting temperature is 1650°C, the heating rate is 50°C / min, and the melting time is 30min. The metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, so that the Al2O3 reinforcement phase grows in situ in the low-density steel melt.
[0115] Step 7: pouring the Al2O3 reinforced low-density steel melt in step 6 into a graphite mold and cooling it at room temperature to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
[0116] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of this embodiment is 12.4wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.82g / cm 3 , tensile strength is 975MPa, elongation is 25.4%, hardness is 318.1HV. The average particle size of Al2O3 reinforcement phase particles is 9.7μm, and the volume percentage of Al2O3 reinforcement phase is 18.5%.
[0117] Comparative Example 1
[0118] This comparative example adopts powder metallurgy to prepare Al2O3 reinforced steel-based composite material, and its preparation process is as follows:
[0119] Step 1: Using iron powder as the matrix and Al2O3 reinforcement phase content of 13wt.%, the matrix iron powder and Al2O3 reinforcement phase are mixed in a container and rotated at a speed of 250 rpm for 30 minutes;
[0120] Step 2: Pressing and molding under a pressure of 750 MPa, sintering in a vacuum tube furnace at 1100° C. at a heating rate of 3° C. / min for two hours, and then furnace cooling to obtain a sample.
[0121] Combination Figure 5 The SEM image of the Al2O3 reinforced steel-based composite material shown in the figure shows that the steel matrix has many defects such as cracks and pores, and the Al2O3 reinforced particles are large in size, with obvious cracks between them and the matrix. The interface bonding strength is weak and it is easy to fall off when subjected to stress, which will lead to the deterioration of the overall performance of the material.
[0122] As shown in Table 1, the Al2O3 reinforced steel matrix composite material prepared in this comparative example uses iron powder as the matrix material, and the Al element is mainly concentrated in the Al2O3 reinforcement phase. The density of the Al2O3 reinforced steel matrix composite material is 7.21 g / cm 3 , tensile strength is 350MPa, elongation is 8%, hardness is 176HV. The average particle size of Al2O3 reinforcement particles is 20μm, and the volume percentage is 12.4%.
[0123] Comparative Example 2
[0124] This comparative example adopts powder metallurgy sintering method to prepare Al2O3 reinforced steel-based composite material, and its preparation process is as follows:
[0125] Step 1: The raw materials are reduced iron powder and alumina powder. 5 vol.%, 10 vol.%, or 15 vol.% of alumina powder and the balance of iron powder are mixed and ground in a mortar for 15 minutes;
[0126] Step 2: Use MY-100 hydraulic press to press the blank with a pressure of 400 MPa and a holding time of 3 minutes to obtain a quasi-20 mm × 5 mm blank.
[0127] Step 3: Under hydrogen protection, the blank is sintered in a high-temperature tubular resistance furnace at a sintering temperature of 1300°C for 3 hours, and then cooled in the furnace to obtain a sintered sample.
[0128] Step 4: The sample with metallic luster was quenched at 900°C for 30 min, and then rapidly cooled with water to obtain Al2O3 reinforced steel-based composite material.
[0129] Combination Figure 6From the microhardness of the Al2O3 reinforced steel-based composites with different Al2O3 additions before and after quenching, it can be seen that the hardness of the Al2O3 reinforced steel-based composites is at most 100HV, which is significantly lower.
[0130] Combination Figure 7 The SEM image of the Al2O3 reinforced steel-based composite material with an Al2O3 addition of 15% is shown. A is the steel matrix and area B is the Al2O3 reinforcement phase. It can be observed from the figure that the material surface is uneven and has many defects. The Al2O3 reinforcement phase is chain-like and has poor bonding with the matrix.
[0131] As shown in Table 1, in this comparative example, the Al2O3 reinforced steel-based composite material prepared with 15 vol.% alumina powder has reduced iron powder as the matrix material, and the Al element is mainly concentrated in the Al2O3 reinforcement phase. The density of the Al2O3 reinforced steel-based composite material is 7.52 g / cm 3 , tensile strength is 410MPa, elongation is 4%, hardness is 60HV. The average particle size of Al2O3 reinforcement phase is 34μm, and the volume percentage is 11%.
[0132] Comparative Example 3
[0133] This comparative example adopts the preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of Example 1, and the differences from Example 1 are as follows:
[0134] In step 1, the mass ratio of copper oxide powder to metal aluminum powder and metal iron powder is 9:4:87.
[0135] In step 6, the mass ratio of the pre-pressed block to the pure aluminum block and the pure iron block is 8:6:94.
[0136] Figure 8 The SEM image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material sample prepared in this comparative example shows that the Al2O3 reinforcement phase content in the sample is low and the distribution is uneven, which will limit its reinforcement effect. When the material is subjected to an external load, the larger reinforcement phases are prone to stress concentration and cracks, affecting the overall performance.
[0137] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in this comparative example is 6.1wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 7.45g / cm 3 , tensile strength is 753MPa, elongation is 22%, hardness is 243HV. The average particle size of Al2O3 reinforcement phase particles is 10.2μm, and the volume percentage of Al2O3 reinforcement phase is 3.5%.
[0138] Comparative Example 4
[0139] This comparative example adopts the preparation method of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material of Example 1, and the differences from Example 1 are as follows:
[0140] In step 1, the mass ratio of copper oxide powder to metal aluminum powder and metal iron powder is 8:3:88.
[0141] In step 6, the mass ratio of the pre-pressed block to the pure aluminum block and the pure iron block is 9:15:85.
[0142] Fig. 9 From the SEM image of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material sample prepared in this comparative example, it can be seen that the average particle size of the Al2O3 reinforcement phase is large, the distribution of elements inside the reinforcement phase is uneven, and intergranular fracture is prone to occur, resulting in poor overall performance of the material.
[0143] As shown in Table 1, the Al content in the steel matrix of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material prepared in this comparative example is 15.03wt.%; the density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.76g / cm 3 , tensile strength is 428MPa, elongation is 2%, hardness is 450HV. The average particle size of Al2O3 reinforcement phase particles is 26μm, and the volume percentage of Al2O3 reinforcement phase is 32.52%.
[0144] Table 1
[0145]
[0146] Combining Table 1, the comparative examples and the embodiments, it can be seen that the Al content in the iron matrix of the in-situ self-generated Al2O3-reinforced low-density iron-based composite material prepared in the embodiment of the present invention is in the range of 8-13wt.%, the volume percentage of the Al2O3 reinforcement phase is in the range of 10-20%, the average particle size of the Al2O3 reinforcement phase is in the range of 5-10μm, and the overall density is in the range of 6.8-7.2g / cm 3 The tensile strength is 800-1000MPa, the elongation is 25%-35%, and the hardness is in the range of 280HV-320HV, which can ensure the low density of steel-based composite materials while improving the tensile strength, elongation and hardness of the material.
[0147] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. An in-situ Al2O3 reinforced low-density steel-based composite material, characterized in that: It includes a steel matrix and an Al2O3 reinforcement phase distributed in the steel matrix; The steel matrix is high-aluminum steel, and the Al content of the high-aluminum steel is 8-13wt.%; The Al2O3 reinforcement phase is generated by in-situ reaction between oxygen elements in the metal oxide molten salt and aluminum elements in the high-aluminum steel melt during the smelting process, and the volume percentage of the Al2O3 reinforcement phase in the steel matrix is 10-20%.
2. The in-situ Al2O3 reinforced low-density steel-based composite material according to claim 1, characterized in that: The metal oxide molten salt is selected from one or more of copper oxide, lanthanum oxide and iron oxide.
3. The in-situ self-generated Al2O3 reinforced low-density steel-based composite material according to claim 1, characterized in that: The average particle size of the Al2O3 reinforcement phase is 5 to 10 μm.
4. The in-situ Al2O3 reinforced low-density steel-based composite material according to claim 1, characterized in that: The density of the in-situ self-generated Al2O3 reinforced low-density steel-based composite material is 6.8-7.2 g / cm 3 , tensile strength is 800~1000MPa, elongation is 25%~35%, and hardness is 280HV~320HV.
5. A method for preparing an in-situ Al2O3 reinforced low-density steel-based composite material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing metal oxide molten salt powder, metal aluminum powder and metal iron powder uniformly by ball milling to obtain a mixed powder; S2, vacuum drying the mixed powder, and adding paraffin wax to the mixed powder for doping; S3, drying the mixed powder doped with paraffin wax in an air environment, then stirring it evenly and pressing it into blocks to obtain pre-pressed blocks; S4, placing the pre-pressed block, pure aluminum block and pure iron block in an induction furnace for smelting, during the smelting process, the metal oxide molten salt reacts with Al in the melt in situ to generate an Al2O3 reinforcement phase, and after the smelting is completed, casting is performed to obtain an in-situ self-generated Al2O3 reinforced low-density steel-based composite material.
6. The method for preparing the in-situ self-generated Al2O3 reinforced low-density steel-based composite material according to claim 5, characterized in that: In step S1: The mass ratio of the metal oxide molten salt to the metal aluminum powder and the metal iron powder is 10-20:10-20:60-80; The particle sizes of the metal oxide molten salt, metal aluminum powder and metal iron powder are all 9 to 20 μm; In the ball milling process, the ball milling time is ≥6 hours, and the ball-to-material ratio is 3 to 15:
1.
7. The method for preparing the in-situ self-generated Al2O3 reinforced low-density steel-based composite material according to claim 5, characterized in that: In step S2: The vacuum degree during vacuum drying is 1×10 -1 ~1×10 2 Pa; The mass ratio of the mixed powder to paraffin is 90-100:
1.
8. The method for preparing the in-situ self-generated Al2O3 reinforced low-density steel-based composite material according to claim 5, characterized in that: In step S3: During the drying process, the drying temperature is 70-100°C; During the pressing process, the pressing pressure is 25-50 MPa.
9. The method for preparing the in-situ self-generated Al2O3 reinforced low-density steel-based composite material according to claim 5, characterized in that: In step S4: The mass ratio of the pre-pressed block, the pure aluminum block, and the pure iron block is 5-7:8-13:87-92; In the smelting process, the smelting temperature is 1550-1650° C., the smelting time is 20-30 min, and the heating rate from room temperature to the smelting temperature is 30-50° C. / min.
Citation Information
Cited By
In-situ synthesis Al2O3 reinforced composite low-density steel and thermal deformation method thereof
CN121737581A
An in-situ self-generated Al2O3 reinforced composite low-density steel and its hot deformation method
CN121737581B